Journalism, separation and independence: Newspaper coverage of the end of the British Mandate for Palestine, 1948. (November 2019) - Rodgers, James
This article examines the reporting of the end in 1948 of the British Mandate for Palestine in both British Newspapers and the New York Times . The research is focused on 50 news items published during the last few weeks of the Mandate, especially on and around 14th May 1948. The article seeks to explore the relationship between correspondents, the British authorities and the people then living in Palestine. The article argues that, despite various factors which might have influenced their work, the correspondents still struggled for, and achieved, a degree of independence in their reporting. In addition to these more overt influences, the article discusses whether correspondents may have been influenced by a broader mindset prevalent at the time in the society to which they belong. In doing so, it employs Edward Said's work on Orientalism, especially where Orientalism 'connotes the high-handed executive attitude of nineteenth-century, and early-twentieth-century European colonialism'. The coverage reveals much about the way the role of Britain in Palestine was portrayed to newspaper audiences at a time when Britain's influence in the wider region was in decline. In conclusion, the article argues that, for all journalism's association with political elites, the best reporting from that time provided its audience with valuable insight into the likely consequences of the end of the Mandate – insight which remains valuable today, especially in the year, 2017, which will see both the centenary and the 50th anniversary of, respectively, Balfour Declaration and the Six-Day War.